2020
DOI: 10.1016/j.jcol.2019.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for tumour response after the neoadjuvant-treatment of rectal adenocarcinoma

Abstract: Purpose  Standard of care for locally advanced rectal cancer is neoadjuvant chemoradiotherapy followed by surgery. This study identified predictive factors for tumour response in our series. Patients and methods  Between January 2005 and December 2018, 292 patients with locally advanced rectal cancer treated by preoperative chemo-radiation before surgery were retrospectively analyzed. The radiation dose was 50.4 Gy with fluoropyrimidine-based chemotherapy regimens. Patients-tumour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Michael J O'Connell et al reported that the addition of oxaliplatin to capecitabine combined with preoperative radiotherapy did not further improve the efficacy but significantly increased the toxicity [26]. However, data from Claus Rödel et al showed that adding oxaliplatin to fluorouracil-based neoadjuvant radiotherapy and adjuvant chemotherapy significantly increased disease-free survival in rectal cancer patients (clinically staged cT3-4 or cN1-2) and could be a new treatment option for locally advanced rectal cancer [25,45]. Regarding the exploration of adding adjuvant chemotherapy after neoadjuvant radiotherapy, a multicenter, phase 2 trial conducted by Julio Garcia-Aguilar et al showed that mFOLFOX6 administered after neoadjuvant radiotherapy may increase the rate of patients achieving pathologic complete response, and a phase 3 clinical trial is currently underway [27].…”
Section: Neoadjuvant Chemoradiotherapymentioning
confidence: 99%
“…Michael J O'Connell et al reported that the addition of oxaliplatin to capecitabine combined with preoperative radiotherapy did not further improve the efficacy but significantly increased the toxicity [26]. However, data from Claus Rödel et al showed that adding oxaliplatin to fluorouracil-based neoadjuvant radiotherapy and adjuvant chemotherapy significantly increased disease-free survival in rectal cancer patients (clinically staged cT3-4 or cN1-2) and could be a new treatment option for locally advanced rectal cancer [25,45]. Regarding the exploration of adding adjuvant chemotherapy after neoadjuvant radiotherapy, a multicenter, phase 2 trial conducted by Julio Garcia-Aguilar et al showed that mFOLFOX6 administered after neoadjuvant radiotherapy may increase the rate of patients achieving pathologic complete response, and a phase 3 clinical trial is currently underway [27].…”
Section: Neoadjuvant Chemoradiotherapymentioning
confidence: 99%
“…Identification of factors that influence histological response can help predict prognosis and propose organ preservation for good responders. Multiple studies have correlated pathological complete response with disease-free survival and overall survival [4][5][6]. It is essential to increase complete pathological responses, but it is unclear what clinical factors are involved.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have evaluated the importance of clinical and pathological markers potentially associated with nCRT response. For instance, the pathological grade, tumor size, clinical stage determined by imaging techniques, pre-treatment levels of the carcinoembryonic antigen (CEA), nCRT and surgery intervals, and tumor budding, among others, may impact the nCRT response ( 1 , 9 11 ). More recently, molecular approaches such as the identification of gene mutations, gene expression profiles ( 12 ), genomic instability ( 13 ), and DNA methylation ( 14 ) have been evaluated in pCR prediction and some frequently mutated genes were identified ( 15 ).…”
Section: Introductionmentioning
confidence: 99%